Pengaruh Dewan Direksi, Struktur Modal Dan Kinerja Lingkungan Terhadap Nilai Perusahaan - Teresa Etin Juwita Diaz; Virna Sulfitri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research examines the influence of the board of directors, capital structure and environmental performance on company value in consumer sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022. The sampling method uses purposive sampling and the method used in this research is multiple linear regression analysis. The number of samples in this research was 32 companies. The findings show that one determinant has a positive effect on company value from the three hypotheses proposed. The board of directors has a positive effect on company value, while capital structure and environmental performance have a negative effect on company value. The practical implications of this research emphasize the important role of the board of directors in increasing company value. Investors will respond to good corporate governance which is proxied through the board of directors as a positive signal that the company is superior to other companies